PENGEMBANGAN SENAM BINA DARMA UNTUK PEMBELAJARAN AKTIVITAS RITMIK PENDIDIKAN JASMANI, OLAHRAGA DAN KESEHATAN - Sukmawati, Noviria (Jurnal Ilmiah Bina Edukasi, 2017)
The purpose of this research is to improve the students' activeness in rhythmic gymnastics through gymnastics Bina Darma. Method used in this research is the development of research methods. the results of questionnaire responses charging towards teachers percentaced analyzed and found that 81% of teachers Penjasorkes gave a positive response and 19% gave a negative response, and the effectiveness of coaching gymnastics darma products received a positive response of students in learning rhythmic activity. Study physical education amounted to 81.33%, while the negative response by 18.66%. Conclusion The effectiveness of the product in the category gymnastics coaching darma very good. gymnastic is feasible and can be used to study physical education at school and in accordance with the standard school curriculum through the process of validation expert and student respondents. The results of this research have proven that coached gymnastics for use in teaching physical education at school.